Sustainable Design and Construction in Africa : A System Dynamics Approach - Dosumu, Oluwaseun; Aigbavboa, Clinton; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2018)
This book addresses some of the countless challenges faced by developing countries when adopting sustainable design and construction and offers suggestions for the way forward for African development projects.The authors argue that the pervasive non-consideration of the interrelationship between the elements of sustainable design and construction is the reason for the current failures in sustainable design and construction in developed countries. By treating sustainability as a complex system, the authors provide the missing link between the design and construction of projects in a sustainable way with a view to improving industry and project performance. In doing so the book posits the need for improved sustainability practice in developing countries, lessons for developing countries from the successes and failures of sustainability adoption by developed nations, factors influencing adoption of sustainability and effects of sustainable designs and construction on productivity, human health and the environment at large. This book will be of interest to construction researchers, practitioners, professional bodies, housing policy makers and government institutions as well as training and funding providers in these areas.
General introduction--The concept of conventional building design and construction -- Project success criteria -- Concept of sustainability in construction -- Successes of sustainable building designs and construction: Lessons from adopters -- Failures of sustainable building designs and construction: Lessons from adopters -- Factors influencing sustainable building designs and construction -- Effects of sustainable design and construction on humans and the environment -- Challenges of sustainable design and construction for developing countries -- Causal loop diagram (CLD) of the relationship among elements of sustainable design and construction -- System dynamics model of the relationship among elements of sustainable design and construction -- The way forward.
Includes bibliographical references and index.
Also available in print format.
Keywords: ARCHITECTURE / Sustainability & Green Design; ARCHITECTURE / Buildings / General; Sustainable buildings -- Africa; Electronic books